3 Stages of a Pan-African Identity Framework for Establishing Self-Sovereign Identity With Blockchain - Darnell, S. Solomon; Sevilla, Joseph (Frontiers in Blockchain, 2021)
The African continent (specifically its overwhelming in(animate) resources) is often referred to as the sleeping giant by magazines, blogs, research presentations and articles, and NGOs (such as World Bank Morris et al. (2009); Cobbing and Hiller (2019)). Reasons for this moniker/title include the continents plentiful natural resources, its large and quickly growing young population, and the young populations quick adoption and acclimatization to technology. Most countries on the continent are known as developing countries due to lack of access to safe drinking water, reliable electricity and roads, sanitation and hygiene, and a high number of people with tropical/infectious diseases. However, due to the usefulness of cellular phones and technology, several countries and companies within them have focused on cell phone proliferation (91% in Kenya). Smart phone usage allows Kenyans access to the world’s information and potentially endless innovation. Given a large number of Kenyans with smartphones use social media coupled with the advent of Europe’s GDPR (general data protection regulation), African identity and its associated data became an area of great interest. As the world is quickly progressing into a digital economy, a solution must be created that allows us to regain and control our identities, doing our best to ensure losing such is infinitely close to computationally and probabilistically impossible/improbable. Developing a blockchain based identity backbone, using biometrics and historical family information while allowing government based identification documents is the best way forward. Three stages have been identified as necessities to accomplish the development of this system, before opening it further beyond the pan African world-wide community. The three stages are defined by systems that allow for biometric/demographic registration (stage 1), interoperability and security hardening (stage 2), and biometric modality data analysis/organization/association (stage 3).